2004
DOI: 10.5713/ajas.2004.514
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Digestibility of Palm Kernel Cake for Muscovy Ducks

Abstract: Expeller pressed and solvent extracted palm kernel cake (PKC) were force-fed to male and female Muscovy ducks at 7 weeks of age. The nutrient digestibility, apparent metabolizable energy (AME), true metabolizable energy (TME) and true available amino acid (TAAA) digestibilities were determined. There was no significant (p>0.05) effect of the type of PKC used on crude protein (CP), ether extract (EE), metabolizable energy (ME) and amino acid (AA) digestibilities. However, digestibilities of dry matter (DM) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Though the palm kernel meal is not widely used in the poultry industry because of its high fibre and low energy contents; the use of PKC in poultry diets has been reported by several researchers (Onwudike, 1986;Mustafa et al, 2004). It has also been reported that enzymes could break down the nonstarch polysaccharides (mannans) into manno-oligosaccharides to improve its nutritional quality (Dusterhoft et al, 1993a, b, c;Daud et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Though the palm kernel meal is not widely used in the poultry industry because of its high fibre and low energy contents; the use of PKC in poultry diets has been reported by several researchers (Onwudike, 1986;Mustafa et al, 2004). It has also been reported that enzymes could break down the nonstarch polysaccharides (mannans) into manno-oligosaccharides to improve its nutritional quality (Dusterhoft et al, 1993a, b, c;Daud et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The 2% of SHMP would be an optimum concentration for PKCP extraction. Molins (1991) reported that phosphate ions increase the solubility of proteins both above and below their isoelectric pH. The repulsion between the groups and chains carrying the same charge forces the protein structure to open up when the phosphate ions and protein are interacting.…”
Section: Resultsmentioning
confidence: 99%
“…They were then force-fed with the specific amounts of diets (all treatments). A stainless steel funnel with a 40-cm stem was used to force-feed (Mustafa et al, 2004). Water was available ad libitum during the experiment.…”
Section: Methodsmentioning
confidence: 99%